Best practice in the management of benign prostatic hyperplasia in the patients requiring anticoagulation. Issue 12 (December 2018) - Heiman, Joshua; Large, Tim; Krambeck, Amy
In today's aging population, urologists are often treating older patients with multiple comorbidities. Lower urinary tract symptoms from benign prostate hyperplasia (LUTS/BPH) is a common condition that affects men, with increasing prevalence as men age. In a subset of patients, the symptoms are too severe or refractory to medical therapy and, therefore, surgical therapy is required to improve their LUTS. The use of medical therapy often delays the need to intervene surgically in men with LUTS/BPH and with advances in the management of cardiovascular disease, urologists are increasingly encountering more men requiring BPH surgery on chronic anticoagulation therapy. The decision of when to offer surgical intervention and how to manage anticoagulation medication in the perioperative setting is a dilemma with which surgeons are dealing with increasing frequency. The purpose of this review is to clarify the optimal approach to the surgical patient with LUTS/ BPH requiring anticoagulation therapy.